Implementation of Neutrosophic Function Memberships Using MATLAB Program - S. Broumi; D. Nagarajan; A. Bakali; M. Talea; F. Smarandache; M.Lathamaheswari; J. Kavikumar (Neutrosophic Sets and Systems, 2019)
Membership function (MF) plays a key role for getting an output of a system and hence it influences system’s performance directly. Therefore choosing a MF is an essential task in fuzzy logic and neutrosophic logic as well. Uncertainty is usually represented by MFs. In this paper, a novel Matlab code is derived for trapezoidal neutrosophic function and the validity of the proposed code is proved with illustrative graphical representation